OS 21-02 CONNECTING TUBULE-GLOMERULAR FEEDBACK (CTGF) IN RENAL HEMODYNAMICS AND BLOOD PRESSURE REGULATION AFTER UNILATERAL NEPHRECTOMY (UNx). (September 2016) - Romero, Cesar; Monu, Sumit; Cabral, Glauber; Knight, Robert; Carretero, Oscar
Abstract : Objective: Renal hemodynamics is critical for regulation of glomerular filtration (GFR), sodium excretion and blood pressure (BP), and it depends on myogenic response, tubuloglomerular feedback (TGF) and connecting tubule-glomerular feedback (CTGF). CTGF dilates afferent arteriole in response to high sodium in connecting tubule (CNT), counteracting and resetting TGF; and increasing the plasma flow and glomerular pressure favoring sodium excretion. CTGF is initiated by epithelial sodium channel (ENaC) activation in CNT and inhibited by ENaC blocker Benzamil. Unilateral nephrectomy (UNx) is accompanied by TGF resetting, increase in renal blood flow (RBF) and single nephron GFR in the remnant kidney, without any changes in systemic BP. We evaluated CTGF role in BP regulation and TGF resetting after UNx. Design and Method: UNx was performed on Sprague-Dawley rats and 24 h later TGF was evaluated in vivo by renal micropuncture using stop flow pressure (Psf) techniques. CTGF was evaluated by intratubularly adding Benzamil during the TGF response. Another set of animals received chronickidney infusion of Benzamil that started 1 week before UNx. Renal blood flow (RBF) was measured by arterial spin labeling-MRI 24 h before and 24 h after the UNx. Direct BP measurement was performed before and 3 weeks after the UNx. Results: After UNx, TGF resetting was observed (delta-Psf 8 ± 1 vs. 1 ± 1 mmHg p < 0.05, Sham vs. Unx) and that was inhibited by Benzamil. RBF increased after the UNx in comparison to sham and this increase was inhibited by chronic infusion of Benzamil (Sham: 305 ± 59; UNx: 456 ± 34; UNx + Benzamil 346 ± 64 ml/min/100 g tissue p < 0.002). Mean BP values were not different between the vehicle or Benzamil infused rats before the UNx, however 3 weeks after the UNx, Benzamil infused rats showed higher mean BP values than vehicle (88 ± 0.3 vs. 97 ± 4 mmHg, p < 0.01). Conclusions: CTGF participates in TGF resetting and BP regulation after UNx. CTGF impairment could be a potential cause of hypertension.